Drawing a pandemic vulnerabilities' map: The SoNAR-global Vulnerabilities Assessment digital and its output - Vaccaro, Concetta; Lenzi, Francesca Romana; Addonisio, Gabriella; Gianfrilli, Daniele; Volkmann, Anna Maria; Napier, David; Giles-Vernick, Tamara (Frontiers in Sociology, 2023)
This paper describes the process, advantages and limitations of a qualitative methodology for defining and analyzing vulnerabilities during the COVID-19 pandemic. Implemented in Italy in two sites (Rome and outside Rome, in some small-medium sized municipalities in Latium) in 2021, this investigation employed a mixed digital research tool that was also used simultaneously in four other European countries. Its digital nature encompasses both processes of data collection Among the most salient is that the pandemic catalyzed new vulnerabilities in addition to exacerbating old ones, particularly economic. Many of the vulnerabilities detected, in fact, are linked to previous situations, such as the uncertainties of labour markets, having in COVID-19 to the greatest negative effects on the most precarious workers (non-regular, part-time, seasonal). The consequences of the pandemic are also reflected in other forms of vulnerability that appear less obvious, having exacerbated social isolation, not only out of fear of contagion, but because of the psychological challenges posed by containment measures themselves. These measures created not mere discomfort, but behavioural changes characterized by anxiety, fearfulness, and disorientation. More generally, this investigation reveals the strong influence of social determinants throughout the COVID-19 pandemic, creating new forms of vulnerability, as the effects of social, economic, and biological risk factors were compounded, in particular, among already marginalised populations.